TEORI DAN KONSEP PEMBAGIAN DAN HIERARKI ILMU MENURUT PERSPEKTIF ISLAM - M. Muslim; Muhammad Arifin; Samudi (An-Nahdlah: Jurnal Pendidikan Islam, 2025)
Knowledge includes all types of knowledge, namely: exact knowledge, language, natural, social, historical, religious and others. People with knowledge are more blessed, more cultured and civilized than those without knowledge. Because of the great function and role given by knowledge, it is not surprising that Allah obliges humans to demand knowledge, cultivate, foster and develop it through research and disseminate and utilize this knowledge for the welfare of human life. The purpose of this study is to examine and analyze the division and hierarchy of knowledge in an Islamic perspective. The research method uses qualitative research with the type of literature through data collection in the form of books, journals and others related to the discussion of this research. While analyzing the data using content analysis. The results of the research found that: The division of knowledge in Islam in the view of al-Ghazali, including: fardu 'ain and fardu kifayah. While seen from its usefulness includes: fadalah, permissible and madzmumah science. While the hierarchy of knowledge in Islam includes: al-ma'rifat, al-'ulum al-naqliyah and al-'ulum al-aqliyah. The hierarchy of knowledge in Islam according to the Sufi view includes: shari'a science, tariqah science, hakikat science and marifat science.